Radiological Features of Bilateral Sequential Leukaemic Optic Nerve Infiltration: A Case Report. (3rd September 2022) - Tong, Jessica Y.; Galanopoulos, Anna; Patel, Sandy; Selva, Dinesh
ABSTRACT: Leukaemic infiltration of the optic nerve is an oncologic emergency that can lead to a significant risk of irreversible vision loss and has an overall poor systemic prognosis. We present the case of a 77-year-old man in previous systemic remission from acute myeloid leukaemia (AML) who developed bilateral sequential leukaemic optic nerve involvement with eventual complete vision loss. A review of the clinical and radiological characteristics of optic nerve infiltration in AML is provided. Profound vision loss to the order of 20/200 or worse is common. Magnetic resonance imaging features include optic nerve thickening, enhancement of the nerve sheath, T2 hyperintensity and restricted diffusion. Urgent orbital radiotherapy is indicated prior to the onset of irreversible optic nerve damage.